Use of HEADSS as a psychosocial screening tool in adolescent patients - Herrera Enriquez, Vannya Cecilia (2024)
Adolescents have diverse and complex healthcare needs, including physical, cognitive, and psychosocial growth and development. In Peru, according to current statistics from the National Survey on Social Relations (ENARES), it is evident that 7 out of 10 adolescents are still victims of physical violence. Psychosocial screening is intended to be an instrument to discriminate risk in adolescents. It evaluates various problems such as depression, suicide, psychosis, anxiety, gangs, as well as alcohol, tobacco, and drug use. Despite its importance, it is often not adequately addressed. In a retrospective study in the United States with hospitalized pediatric patients, psychosocial screening is adequately completed in only 5.3%, showing the little importance given to preventive medicine. Because of this, the application of psychosocial screening in other areas has been sought. In Canada, a prospective study showed the potential of using screening in the emergency department, improving the uptake of at-risk patients.